Persepsi Masyarakat Terhadap Keberadaan Penyuluh Agama Hindu Di Kecamatan Denpasar Selatan - I Gusti Ayu Putu Darmi Astuti; I Nengah Aryanatha; Ni Made Budiasih (Jurnal Penelitian Agama Hindu, 2019)
The phenomenon of the existence of Hinduism Extension workers civil servants and non civil and social religious civil servants in modern times is an interesting theme to be studied, the fact that people in South Denpasar Subdistrict cannot avoid modernity is where the role of extension workers in providing guidance and counseling to Hinduism is required. able to improve the quality of religious life. Digging and dissecting the formulation of predetermined problems using three theories are: (1) theory of existence, (2) perception theory, and (3) theory of communication barriers. This study uses research methods which include: research approaches using qualitative methods. The research location is in the District of Selatan Denpasar. Types and sources of data used are types of qualitative data, while data sources used are primary and secondary data. The technique of determining the informants used is purvitative sampling. Data collection techniques include: observation techniques, interviews, literature, and documentation. The results of the analysis obtained from this study are 1) the existence of Hinduism extensionists. In this task, the Hinduism Extension has 5 (five) functions, namely, administrative, educative, facilitative, consultative, and transformative. Potential This fostered area is classified as a densely populated urban area and a high level of religious heterogeneity. The need for worship facilities and infrastructure is sufficient. The number of Hinduism Religious instructors in the City of Selatan Denpasar is as many as 2 Hindu Religion Extension Servants PNS and 16 Non-PNS Hindu Religion Extension. 2) Community perception is categorized into, a). Perceptions of community leaders, b). Stakeholder Perception, c). sekaa perception, d). widyasabha perception. Perception is seen as the most important component in the delivery of information. Through the public perception can be realized, can understand about the condition of the community in 10 villages / villages in Selatan Denpasar. The community can reveal how the performance of the Hindu Religious Extension in each of the target areas 3) internal and external constraints that occur when coaching Hinduism.